Analisis Pelayanan Publik Pada UPT.Pengelolaan Perhubungan Wilayah I Dinas Perhubungan Provinsi Riau - Dila Erlianti; Lilis Wahyuni; ERA KACHINTA RIA (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
Public services are indicators of government performance in providing services to the community. This research aims to analyze the quality of public services at the Regional I Transportation Management UPT of the Riau Province Transportation Service, especially in the transportation sector. The research method uses a qualitative approach with data collection techniques in the form of interviews, observation, and documentation. This research evaluates service quality using five indicators: reliability, responsiveness, assurance, attention, and tangible. The research results show that UPT Transportation Management Region I has several advantages in terms of reliability and responsiveness of officers. However, there are several significant weaknesses such as the lack of adequate waiting rooms, special lanes for people with disabilities, and notification sirens. The absence of these facilities has an impact on passenger discomfort and reduces public confidence in the services provided. Reliability, most passengers feel that the service promised by officers is good enough, yet there is still a need for improvement in time management and clarity of service schedules. Responsiveness, officers show a willingness to help passengers, but communication between officers needs to be improved, especially during busy conditions. Guarantees, the knowledge and competence of officers are considered adequate, but further training is still needed. The main shortcomings lie in the tangible aspects and attention to passengers, such as the lack of adequate waiting rooms and special lanes for the disabled. The conclusion of this research emphasizes the need for improvements in tangible aspects and attention to improve the quality of public services. The recommendations given include the provision of waiting rooms, special disability lanes, and health clinics, as well as communication tools and notification sirens. It is hoped that with these improvements, the quality of public services at UPT Transportation Management Region I can improve significantly and meet community expectations.